Distance learning : principles for effective design, delivery, and evaluation - Mehrotra, Chandra (SAGE Publications, 2001)
What delivery methods are available to make education accessible to a wide variety of potential learners? What are their strengths and weaknesses? How can instructors create effective learning environments in distance courses? What support from administrators and staff is essential? What guidelines are used by accrediting agencies to assure program quality? This highly readable book by three experienced faculty members answers these questions and more. Both theoretical and practical, the book presents proven principles and research-based advice. Drawing upon their experience with a var.